2017
DOI: 10.1002/chem.201606036
|View full text |Cite
|
Sign up to set email alerts
|

Use of Charge‐Charge Repulsion to Enhance π‐Electron Delocalization into Anti‐Aromatic and Aromatic Systems

Abstract: A series of 9-fluorenyl cations has been studied and it is shown that increasing charge on a heterocyclic substituent group enhances the anti-aromatic character of the carbocation system. Similarly, a series of dibenzosuberenyl cations has been studied and increasing charge on a substituent group is shown to enhance aromatic character in the carbocation system. These studies include the direct observations of dicationic and tricationic species using stable-ion conditions and low temperature NMR. The structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Our previous study showed that dicationic fluorenyl cations could be generated conveniently through the condensation of diaryl ketones in superacid [8,9]. The required ketones (4) have been prepared via two routes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study showed that dicationic fluorenyl cations could be generated conveniently through the condensation of diaryl ketones in superacid [8,9]. The required ketones (4) have been prepared via two routes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The chemistry involves formation of the superelectrophilic fluorenyl cation 2 from condensation of the 2-pyridyl ketone in the superacid. Using stable ion conditions and low temperature 13 C NMR, the dicationic species (2) was directly observed [9]. We demonstrated that the dication 2 was a useful electrophile for reactions with carbon nucleophiles such as benzene.…”
Section: Introductionmentioning
confidence: 94%
“…This tricationic species has been directly observed by low temperature NMR using stable ion conditions. 17 Reaction with benzene gives 34 as the final product. The condensation chemistry was also adapted to a polymer synthesis wherein the fluorene ring system is part of the polymer backbone.…”
Section: Methodsmentioning
confidence: 99%
“…Dehydration through the oxonium ion 26 leads to the highly electrophilic fluorenyl ion 27 . This tricationic species has been directly observed by low temperature NMR using stable ion conditions [ 31 ]. Reaction with benzene gives 28 as the final product.…”
Section: New Types Of Superelectrophilesmentioning
confidence: 99%